ANALISIS RESEPSI TERHADAP REPRESENTASI HIDUP HEMAT PADA FILM KELUARGA SUPER IRIT - Putri Aniisah; Ririn Puspita Tutiasri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze audience reception of the representation of frugal living in the film Keluarga Super Irit. The research employs a descriptive qualitative method using a reception analysis approach based on Stuart Hall's encoding-decoding theory. The film Keluarga Super Irit experienced by middle-class families in coping with economic pressures through various frugal living practices depicted throughout the story. The findings reveal that audiences interpret the representation of frugal living in diverse ways, which are reflected in the dominant-hegemonic, negotiated, and oppositional positions, depending on each informant's background, experiences, and personal values.